EFEKTIVITAS PEMBELAJARAN BERBASIS PROYEK TERHADAP PENINGKATAN BERPIKIR KREATIF SISWA PADA MATEMATIKA - Muasyaroh, Alfi; Afandi, Muhammad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research focuses on the influence of the project based learning model on students' creative thinking abilities in fifth grade mathematics at SDN Paseban, Kebunagung, Demak. The aim of this research is to determine the effect of the project based learning model on the creative thinking abilities in mathematics of fifth grade students at SDN Paseban. This research uses a quasi experimental design. This research uses a Prettest-Posttest Only Control Group Design research design using pre-test and post-test as the basis for data collection. The population and sample used were fifth grade students at SDN Paseban using saturated sampling techniques. Based on the research results, there is an influence of the project based learning model on creative mathematical thinking abilities obtained from the pretest results of 61.88 and the posttest results of 85.77 and the results of inferential statistical calculations obtained tcount = 6,567 and ttable = 2,364 tcount > ttable or 6,567 > 2,364 and the sig value (2-failed) is 0.001. then we get sig. (2-failed) < 0.05 then Ho is rejected and H1 is accepted. This means that there is a significant influence on the average test score before and after treatment. Based on the tests above, it shows that there is an influence of the PjBL learning model on students' creative thinking abilities in fifth grade mathematics at SD N Paseban.